WANDERING THYROID FOLLICLES WITHIN THE RENAL TISSUE OF CARP FISH "Cyprinus Carpio". - Amer M. Hussin (Basrah Journal of Veterinary Research)
Twenty healthy adult Carp fish were collected from Dijlah river in Iraq in Summer and winter times of the year (Ten for each ). The fish were sacrificed and fixed in 10% neutral buffered formalin solution. Routine histological preparations were carried out. Hematoxylin - Eosin stain was used. The finding of the current study showed that clear connective tissue capsule was not observed. Instead, wide loose connective tissue was surrounded the follicles. The thyroid follicles were distributed individually or in groups in the kidney and sub pharyngeal region( around the ventral aorta). The thyroid tissue was represented by thyroid follicles of different sizes and shapes. In Carp fish, the building up and organization of the follicular cells of thyroid follicles were simple and poorly organized. There was a close relationship between the morphological state of thyroid follicles and the season( temperature). The results of the present study also demonstrated that the spread of thyroid follicles in summer was more than in winter where the follicles appeared as aggregated at the periphery of renal tissue and also the results of this study showed that large and small follicles were combined. The study also registered that, during winter, the large follicles were mostly formed by the aggregation of smaller ones and that according to the physiological status of the thyroid tissue. The study concluded firstly that these follicles had the ability to wandered within the renal tissue. Moreover, the study concluded that the thyroid follicle was dynamic structure, and their sizes depending on the amount of colloid present within .